2010
DOI: 10.1021/ic9024052
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Metal Alkyl, Amido, and Cyclopentadienyl Complexes Supported by Imidazolin-2-iminato Ligands: Synthesis, Structural Characterization, and Catalytic Application

Abstract: The rare earth metal dichlorides [(1)MCl(2)(THF)(3)] (2a, M = Sc; 2b, M = Y; 2c, M = Lu) and the gadolinium complex [(1)GdCl(2)(THF)(2)] x [LiCl(THF)(2)] (2d), containing the 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-iminato ligand 1, proved to be versatile starting materials for the preparation of trimethylsilylmethyl ("neosilyl") and bis(trimethylsilyl)amido complexes [(1)M(CH(2)SiMe(3))(2)(THF)(2)] (3a-3d) and [(1)M(HMDS)(2)(THF)] [4a-4d, HMDS = hexamethyldisilazide, N(SiMe(3))(2)] and for the preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 201 publications
2
53
0
Order By: Relevance
“…It was also the pioneering work of Hou that showed that hydrogenolysis of the dialkyls leads to the corresponding dihydrides. Remarkably, the structure of these complexes proved to be based on novel, polynuclear cluster framework, such as tetranuclear [(C 5 Me 4 SiMe 3 )LnH 2 ] 4 (THF) 0e2 and hexanuclear [(C 5 Me 5 )LnH 2 ] 6 [13,14] and, equally notable was the unprecedented reactivity of these polyhydrides, for example toward nitriles [15a] and carbon monoxide [15b].…”
Section: Introductionmentioning
confidence: 99%
“…It was also the pioneering work of Hou that showed that hydrogenolysis of the dialkyls leads to the corresponding dihydrides. Remarkably, the structure of these complexes proved to be based on novel, polynuclear cluster framework, such as tetranuclear [(C 5 Me 4 SiMe 3 )LnH 2 ] 4 (THF) 0e2 and hexanuclear [(C 5 Me 5 )LnH 2 ] 6 [13,14] and, equally notable was the unprecedented reactivity of these polyhydrides, for example toward nitriles [15a] and carbon monoxide [15b].…”
Section: Introductionmentioning
confidence: 99%
“…All aminoalkenes were distilled from CaH 2 under reduced pressure or under an argon atmosphere and stored in the glove box, for details see ref 10. Aminoalkenes 2,2‐diphenyl‐4‐pentenyl‐1‐amine ( 5 ),26 2‐methyl‐2‐phenyl‐4‐pentenyl‐1‐amine ( 7 ),7c 2,2‐diphenyl‐5‐hexenyl‐1‐amine ( 13 ),27 1‐methylpent‐4‐enylamine ( 15 ),28 2,2‐dimethyl‐4‐pentenyl‐1‐amine ( 9 ) and 2‐methyl‐4‐pentenyl‐1‐amine ( 11 )29 were prepared as described in the literature. The spectral data for the cis‐ and trans‐ isomers of 2,5‐dimethylpyrrolidine ( cis ‐ 16 and trans‐ 16 )28 were entirely consistent with those described in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Aminoalkenes 2,2‐diphenyl‐4‐pentenyl‐1‐amine ( 5 ),26 2‐methyl‐2‐phenyl‐4‐pentenyl‐1‐amine ( 7 ),7c 2,2‐diphenyl‐5‐hexenyl‐1‐amine ( 13 ),27 1‐methylpent‐4‐enylamine ( 15 ),28 2,2‐dimethyl‐4‐pentenyl‐1‐amine ( 9 ) and 2‐methyl‐4‐pentenyl‐1‐amine ( 11 )29 were prepared as described in the literature. The spectral data for the cis‐ and trans‐ isomers of 2,5‐dimethylpyrrolidine ( cis ‐ 16 and trans‐ 16 )28 were entirely consistent with those described in the literature. The diastereoselectivity for the cyclization of 15 to trans‐ 16 and cis ‐ 7f was determined based on 1 H NMR integration; trans ‐16 / cis ‐16 =3.14 (septet)/2.93 (m) for NCH peaks.…”
Section: Methodsmentioning
confidence: 99%
“…REEs have attracted attention and aroused high interest in applying them in a variety of fields. Among them, the use of Sc has continuously increased in many application areas, such as scandium-aluminum alloys [1][2][3], where a Sc content of 2% by weight can make the alloys much stronger than other high-strength alloys, and minor amounts of high-purity Sc are used in semiconductors [4], specialty lighting [5,6], and catalysts [7,8]. Furthermore, new demands of Sc are expected to come from future fuel-cells [9,10], the aerospace industry and specialty metal alloys [2,3].…”
Section: Introductionmentioning
confidence: 99%